A Re‐examination of Disclosure Level and the Expected Cost of Equity Capital - Botosan, Christine A.; Plumlee, Marlene A. (Journal of Accounting Research, 2002)
This paper examines the association between the cost of equity capital and levels of annual report and timely disclosure, and investor relations activities. We estimate the cost of equity capital using the classic dividend discount model. We find that the cost of equity capital decreases in the annual report disclosure level but increases in the level of timely disclosures. The latter result is contrary to theory but is consistent with managers’ claims that greater timely disclosures may increase the cost of equity capital, possibly through increased stock price volatility. We find no association between the cost of equity capital and the level of investor relations activities. We conclude that aggregating across different disclosure types results in a loss of information. Failing to include all disclosure types in regression analyses may lead to a correlated omitted variable bias and erroneous conclusions.